FENOMENA KOMUNIKASI KELUARGA POLIGAMI DI PEKANBARU - Marselina, Riska; Salam, Noor Efni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Polygamous marriage is a difficult thing to go through because not only differences in opinions expressed in them but especially the feelings of sacrifice for a wife who must be willing to share her husband with another. The purpose of a person to perform marriages and to establish a more intimate relationship is to get a place in outer and inner happiness and a shared sense of both joy and sorrow. The authors study aimed to uncover the motives, meaning and practice of communication three polygamous family in Pekanbaru.This study uses qualitative with phenomenological approach. Subjects were 3 (three) polygamous family in Pekanbaru category are determined by purposive sampling. The collection of data obtained through in-depth interviews, and documentation.These results indicate that the motive for polygamous couples in Pekanbaru consists of Because motive that is compassion, a sense of disappointment, feeling humiliated, economy and affection. While in order to motive that is fixed along and intact, stay in touch with the good, and some that want to split up. Meanings given by a family member against a polygamous marriage in which they live that polygamy is something that is helping, polygamy taught for sincere and sharing, polygamy is something embarrassing, polygamy as a home wrecker, polygamy only cause resentment, and polygamy adversely affected children. The communication experience is categorized into two, namely a pleasant communication experience as mutual understanding, openness, mutual forgiveness and a sense of mutual respect for each other. Related to the communication experience unpleasant as disharmonious relationships, must be willing to share, a mockery of the environment.Keyword: phenomenology, polygamy, motive, signification, communication experience